ANALYSIS OF THE IMPLEMENTATION OF STANDARD OPERATING PROCEDURE, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AND WORK COMPETENCY TOWARDS PRODUCTIVITY AND EMPLOYEES PERFORMANCE OF SURABAYA MERCHANT MARINE POLYTECHNIC - Ardiana, I Dewa Ketut Raka; Andjarwati, Tri; Wulandari, Astrie Deny (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
This study aims to analyze how the influence of the Implementation of Standard Operating Procedure (SOP), Organizational Citizenship Behavior (OCB), and Work Competence on Productivity and Performance of Politeknik Pelayaran Surabaya Employees. The population of the object of research amounted to 150 employees and 110 employees took a sample using the calculation of Slovin formula with a statistical error rate of 5%. The scope of this research is focused on discussions relating to the application of Standard Operating Procedures (SOP), Organizational Citizenship Behavior (OCB), work competence, and productivity that affect employee performance. This type of research is quantitative research, which is based on respondents' answers using a questionnaire with a Likert scale. Interview and observation techniques as a support method to complete research analysis in measuring variables. The test and analysis process is carried out with Structural Equation Modeling (SEM) using the SMARTPLS software. The results of the analysis of this study indicate that the performance of Politeknik Pelayaran Surabaya employees is significantly positively influenced by the application of SOPs, work competence, and productivity. Whereas the OCB does not significantly influence the performance of the Politeknik Pelayaran Surabaya employees.